Refolding and purification of recombinant L-asparaginase from inclusion bodies of E. coli into active tetrameric protein - Upadhyay, Arun K.; Singh, Anupam; Mukherjee, K. J.; Panda, Amulya K. (Frontiers in Microbiology, 2014)
A tetrameric protein of therapeutic importance, Escherichia coli L-asparaginase-II was expressed in Escherichia coli as inclusion bodies (IBs). Asparaginase IBs were solubilized using low concentration of urea and refolded into active tetrameric protein using pulsatile dilution method. Refolded asparaginase was purified in two steps by ion-exchange and gel filtration chromatographic techniques. The recovery of bioactive asparaginase from IBs was around 50%. The melting temperature (Tm) of the purified asparaginase was found to be 64°C. The specific activity of refolded, purified asparaginase was found to be comparable to the commercial asparaginase (190 IU/mg). Enzymatic activity of the refolded asparaginase was high even at four molar urea solutions, where the IB aggregates are completely solubilized. From the comparison of chemical denaturation data and activity at different concentrations of guanidine hydrochloride, it was observed that dissociation of monomeric units precedes the complete loss of helical secondary structures. Protection of the existing native-like protein structure during solubilization of IB aggregates with 4 M urea improved the propensity of monomer units to form oligomeric structure. Our mild solubilization technique retaining native-like structures, improved recovery of asparaginase in bioactive tetrameric form.